Study on HTV silicone rubber material's aging characteristics and assessment method - Xia, Yanwei; Jia, Boyan; Liu, Jie; Chen, Can; Xilin, Wang; Xu, Chi; Jia, Zhidong (Proceedings (International Conference on Properties and Applications of Dielectric Materials. Print), 2018)
In China, High Temperature Vulcanized (HTV) silicone rubber is the widely used as external insulation of composite insulators. After long-time operation, the silicone rubber sheds are generally found aging, which could influence the operation condition of composite insulators significantly. In this paper, to study the characteristics of aging HTV silicone rubber sheds, multiple material analysis methods such as FTIR, XPS, XRD and TG have been conducted on the external and internal layer of specimens. Changes of organic functional groups, element contents, micro-structure have been revealed through the analysis. Finally, quantitative correlation between HTV silicone rubber's organic content and its actual service time has been established based on statistical methods, which could provide a possible way for composite insulator's operation condition assessment.